An improved APIT node self-localization algorithm in WSN - Yong Zhou; Xin Ao; Shixiong Xia (2008 7th World Congress on Intelligent Control and Automation, 2008)
Node self-localization is one of the important research topics in WSN. APIT is a major range-free localization algorithm. Compared with other range-free algorithms, APIT can achieve more high precision position estimation with small communication cost. However, APIT requires high anchor node density. Besides, in the process of APIT test, it is easy to increase InToOut error and OutToIn error. In allusion to these flaws, based on APIT, this paper expands the definition of neighbor node and import neighbor legality inspection and proposes an improved APIT node self-localization algorithm in WSN. Simulation results show that the improvements to APIT test can reduce the IntoOut error and OutToIn error effectively, and improve the precision of position estimation.